Mass Spectrometry for Analysis of Cancer Biomarker from Human Plasma - Yeong Hee Ahn; Kwang Hoe Kim; Park Min Shin; Eun Sun Ji; Jong Shin Yoo (Journal of Analytical Science and Technology, 2011)
Mass spectrometry (MS) can identify new proteins and assay the amount of the biomarker proteins that need to be validated as a viable cancer candidate. Low abundant peptides from plasma glycoprotein were identified by ultra high resolution 15T MALDI-FTICR MS with stable isotope standards and capture by anti-peptide antibodies. For the quantitation of the low abundant biomarkers, multiple reaction monitoring (MRM) method with ESI was applied for human plasma.